Advokasi Untuk Mengurangi Stigma Dan Diskriminasi Terhadap Perempuan Dengan HIV/AIDS - Negoro, Al Banda Arya Rekso; Apsari, Nurliana Cipta; Taftazani, Budi Muhammad (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2024)
This article examines the role of advocacy in reducing stigma and discrimination against women living with HIV/AIDS. Despite the progress made in addressing this issue, stigma and discrimination continue to pose significant challenges for women with this condition, undermining their confidence and participation in social and economic life. Advocacy is identified as a crucial strategy in addressing these issues, through raising public awareness, providing social support, and advocating for the reform of discriminatory policies. This article also discusses interventions such as public education programs and support groups, which are effective in reducing stigma and discrimination. The research method employed is a literature review, which provides a comprehensive overview of the role of advocacy and offers guidance for researchers and activists in addressing this issue. In the discussion, this article posits that advocacy can alter public attitudes, advocate for the rights of women with HIV/AIDS, and promote a more comprehensive understanding of this condition. Furthermore, advocacy can combat stigma and gender discrimination through public campaigns, discussion forums, and educational programs. This article offers insights into the significance of advocacy in reducing stigma and discrimination against women with HIV/AIDS, as well as outlining tangible measures to enhance the protection of their rights.